A dual response organogel system based on an iridium complex and a Eu(iii) hybrid for volatile acid and organic amine vapors. Issue 20 (9th May 2017) - Cao, Xinhua; Zhao, Na; Zou, Guodong; Gao, Aiping; Ding, Qianqian; Zeng, Guanjie; Wu, Yongquan
Abstract : A thiophene-based hybrid organogel system consisting of complex iridium (Ir ) and EuCl3 ·6H2 O can response to volatile acids and organic amine vapors. Abstract : A thiophene-based hybrid organogel system consisting of complex iridium (Ir ) and EuCl3 ·6H2 O was designed and synthesized to realize dual responses to volatile acids and organic amine vapors. The photophysical properties and self-assembly of compound1 and the hybrid organogel were also studied. Compound1 could gelate some organic solvents and self-assemble into 3D nanofibers in the gels. The stable hybrid organogel1-Ir-Eu could be obtained after addition of complexIr and EuCl3 ·6H2 O. FTIR spectral results showed that the hydrogen bond still remained even upon addition of complexIr, EuCl3 ·6H2 O, NaOH and CF3 COOH to organogel1 . Interestingly, the emission properties of the hybrid organogel1-Ir-Eu could undergo interconversion between cyan light and red light via addition of NaOH and CF3 COOH. The emission properties of xerogel film1-Ir-Eu obtained in the presence of NaOH could also undergo fast and reversible transition in response to volatile acids such as CF3 COOH, formic acid, acetic acid, propionic acid and organic amine vapors such as ammonium hydroxide, Et3 N, tripropylamine, and ethylenediamine. The emission spectral change ofIr-Eu in the organogel or xerogel in the presence of base and acid demonstrated the formation of a new complex between complexIr and EuCl3 ·6H2 O. This dual-response process could be repeated many times. Contact angle experiment results further showed the morphology and internal components of the xerogel film surface in the process of response to gaseous CF3 COOH and Et3 N. This work provides a method for producing multifunctional supramolecular materials for sensing volatile acids and organic amine vapors.